KINERJA KEPOLISIAN DALAM UPAYA PENCEGAHAN DAN PENANGGULANGAN TINDAK PIDANA PERJUDIAN TOGEL DI WILAYAH HUKUM KEPOLISIAN RESORT GIANYAR - Indah Purwita Sari, Ni Wayan; Artadi, I Ketut (Kertha Wicara : Journal Ilmu Hukum, 2014)
Gambling is not a new thing for the people of Indonesia, because gambling games have been around since the first and evolve with the changing times. The crime of gambling toggle that much going on in the region is very disturbing public Gianyar. The problem of gambling in Gianyar very disturbing comfort and safety for the community. Purpose of the study is to examine the causes of gambling toggle and to determine remedies undertaken by the Police in preventing and combating gambling toggle. Types of research used in this paper is the kind of empirical legal research objects that have a study of people’s behavior arising from the interaction of existing norms hearing system. Regulated forms of gambling in the book into two KUHP in the article 303, where gambling is included as a crime. Based on research obtained answer factor causing gambling toggle there are two internal and eksternal factor. Legal efforts made by the Police to prevent and cope with two gambling toggle efforts preventive and repressive measures. So the action taken by the Police Resort Gianyar in the prevention and control of gambling toggle such preventive efforts and the efforts of repressive.
Keywords: Crime, Gambling, Remedies